Piezo-force and Vibration Analysis of ZnO Nanowire Arrays for Sensor Application. (2016) - Christian, B.; Volk, J.; Lukàcs, I.E.; Sautieff, E.; Sturm, C.; Graillot, A.; Dauksevicius, R.; O'Reilly, E.; Ambacher, O.; Lebedev, V.
Abstract: To estimate the potential of ZnO nanostructures for force sensing applications, arrays of single nanowires and arrays of nanowire bundles have been fabricated by wet chemical growth method. The piezoelectrical and electrical properties of the single nanowires have been investigated by atomic force microscopy based techniques. The piezoelectric constant d 33 = 15 pm/V has been determined from vibration analyses. The electrical response in the range up to 400 fA upon applying force between 40 nN and 1 μN has been recorded. The nanowire bundles were studied by electro-mechanical macro probing technique within the force range 1 - 10 mN, where a reproducible response in pA range has been measured.